The causal effect of new energy logistics vehicle policies on respiratory disease mortality rate - Zhang, Wei; Liu, Feng; Liu, Nana; Hou, Xiaoran (Frontiers in Public Health, 2025)
IntroductionAmid escalating global efforts to address climate change and persistent threats to public health, evaluating the health benefits of environmental policies is of growing significance.MethodThis study leverages the “Green Freight Distribution Demonstration Project” launched in 2018 as a quasi-natural experiment. Utilizing multi-city panel data from China spanning 2011 to 2024, it employs both a Difference-in-Differences (DID) model and a Double Machine Learning (DML) model to rigorously assess the causal impact of policies promoting new energy logistics vehicles on the mortality rate from respiratory diseases among residents.ConclusionThe findings reveal that the policy significantly reduces respiratory disease mortality rate in pilot cities, a conclusion that remains robust across multiple sensitivity analyses. In terms of mechanisms, the policy directly increases the market penetration of new energy logistics vehicles while reducing the share of the secondary industry (SI). Indirectly, it facilitates the low-carbon transition of urban industrial structures, significantly lowering sulfur dioxide (SO2) concentrations and improving overall air quality, thus contributing to better public health outcomes. Furthermore, the health benefits demonstrate notable heterogeneity: the mortality reduction effect is more pronounced in cities characterized by lower economic development, higher initial pollution levels, and limited medical resources. This study not only provides empirical evidence for quantifying the health dividends of environmental policies but also offers scientific guidance for optimizing green transportation initiatives and achieving integrated governance of environmental and public health goals.